Modeling and Control of Electrostatically Actuated RF-MEMS Switches - Awad, Omar A. H. (2014)
A Master of Science thesis in Mechanical Engineering by Omar A. H. Awad entitled, "Modeling and Control of Electrostatically Actuated RF- MEMS Switches," submitted in February 2014. Thesis advisor is Dr. Ameen El Sinawi and co-advisors are Dr. Maher Bakri-Kassem and Dr. Taha Landolsi. Available are both soft and hard copies of the thesis.